Comparison of trends in the Hadley circulation between CMIP6 and CMIP5 - Xia, Yan; Hu, Yongyun; Liu, Jiping (Science bulletin, 2020)
There have been extensive studies on poleward expansion of the Hadley cells and the associated poleward shift of subtropical dry zones in the past decade. In the present study, we study the trends in the width and strength of the Hadley cells, using currently available simulation results of the Coupled Model Intercomparison Project Phase-6 (CMIP6), and compare the trends with that in CMIP5 simulations. Our results show that the total annual-mean trend in the width of the Hadley cells is 0.13° ± 0.02° per decade over 1970–2014 in CMIP6 historical All-forcing simulations. It is almost the same as that in CMIP5. The trend in the strength of the Northern-Hemisphere (NH) cell shows much greater weakening in CMIP6 than in CMIP5, while the strength trend in the Southern-Hemisphere (SH) cell shows slight strengthening. Single-forcing simulations demonstrate that increasing greenhouse gases cause widening and weakening of both the NH and SH Hadley cells, while anthropogenic aerosols and stratospheric ozone changes cause weak strengthening trends in the SH cell. CMIP6 projection simulation results show that both the widening and weakening trends increase with radiative forcing.